The mobile health application can add our insight into caring for children: The benefit and future usage of the Chemo Assist for Children - Dwi Novrianda; Rika Sarfika (Faculty of Nursing Universitas Padjadjaran, 2023)
Background: The ease of use of mobile health applications felt by users is essential to ensure the sustainability of digital-based intervention programs. The mHealth Chemo Assist for Children (CAC) application has been used by parents with children with acute lymphoblastic leukemia (ALL) who are undergoing chemotherapy in usability tests and positive benefits felt by users have been reported. A deeper understanding of the barriers and factors supporting implementing the CAC mHealth application can help guide strategies to overcome these challenges. Purpose: This study aims to evaluate the obstacles and factors supporting implementing mHealth CAC application in a natural setting. Methods: Qualitative research was conducted at two government hospitals in Indonesia. Focus group discussions were conducted with nine parents of children with ALL following chemotherapy. The interview was transcribed verbatim and analyzed using qualitative content analysis. Results: This research produced three main themes, namely the use of CAC and additional usage expectations, application quality, and current and future application usage. Conclusions: It is necessary to improve the benefit, ease of use of application features and overcome the obstacles experienced in using the CAC application.